Pemanfaatan Fitoterapi Sebagai Imunomodulator Pada Masa Pandemi Covid-19 Di Kelurahan Sukodono Kabupaten Gresik - Suwanto, Suwanto; Ernawati, Ernawati; Yusa, Ali; Faria, Niswatun; Thoyyib Shofi, Ahmad; Purbasari, Setiya (Duta Abdimas, 2022)
Background, the corona virus infection disease can be caused by the covid-19 virus, the first time the corona virus was found in the city of Wuhan, China. The disease quickly spread in various countries. Efforts to prevent the spread of COVID-19 through discipline to health protocols. In addition to implementing public health protocols, it can increase body immunity, increase the immune system through the use of medicinal plants such as; kencur, cardamom, turmeric, lempuyang, ginger, and galangal.The aim is to provide knowledge to extension participants about the use of phytotherapy as an immunomodulator during the COVID-19 pandemic in Sukodono sub-district, Gresik district.Implementation methods include; (1) socialization is carried out by the service team with the government. (2) implementation of activities using lecture, practice, and discussion methods. (3) evaluation of activities through pre-test and post-test to the participants of the extension agent. The evaluation results were analyzed using a paired sample T test with a significance level (Î± 0.05). Service activities in Sukodono sub-district, Gresik district, with a total of 30 participants. The results, based on the analysis of the paired T test, the average pre-test score was 52.13, the post-test score was 87.20. while the value of sig 2 tailed shows 0.000 < 0.05.In conclusion, there was an increase in knowledge of participants after being given counseling about the use of phytotherapy as an immunomodulator during the covid-19 pandemic.